2020
DOI: 10.1155/2020/8791657
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of the Ethyl Acetate Part of Er MiaoSan on Adjuvant Arthritis Rats by Regulating the Function of Bone Marrow‐Derived Dendritic Cells

Abstract: Aims. The aim of this study was to evaluate the protective effects of Er Miao San (EMS) and the regulative function of bone marrow-derived dendritic cells (BMDCs) on adjuvant arthritis (AA) in rats. Methods. The ethyl acetate part of EMS (3 g/kg, 1.5 g/kg, and 0.75 g/kg) was orally administered from day 15 after immunization to day 29. The polyarthritis index and paw swelling were measured, the ankle joint pathological changes were observed using hematoxylin-eosin (HE) staining, and the spleen and thymus index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…One specimen of each (ID: EMS-19-01) was preserved in the Herbarium of Pharmacy, School of Pharmacy, Anhui University of Traditional Chinese Medicine (Hefei, China). The extraction method can be found in our group's previous research 15 .…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…One specimen of each (ID: EMS-19-01) was preserved in the Herbarium of Pharmacy, School of Pharmacy, Anhui University of Traditional Chinese Medicine (Hefei, China). The extraction method can be found in our group's previous research 15 .…”
Section: Molecular Dockingmentioning
confidence: 99%
“…EMS has been used for the treatment of immunological liver injury 13 and hyperuricemia 14 . Meanwhile, an increasing number of studies have shown that EMS is one of the classic prescriptions for the treatment of RA 15 . We previously reported that EMS could signi cantly reduce pathological changes, regulate the balance of cytokines and attenuate synovial hyperplasia and in ammatory cell in ltration in joint tissues in AA rats.…”
Section: Introductionmentioning
confidence: 99%